Zearalenone and its metabolites in the tissues of female wild boars exposed per os to mycotoxins. (May 2016) - Gajęcka, Magdalena; Sławuta, Piotr; Nicpoń, Jakub; Kołacz, Roman; Kiełbowicz, Zdzisław; Zielonka, Łukasz; Dąbrowski, Michał; Szweda, Wojciech; Gajęcki, Maciej; Nicpoń, Józef
Abstract: The study was performed on 18 clinically healthy female wild boars with initial body weight of 35 ± 2 kg. The animals were divided into two experimental groups (group I and group II) and one control group (group C) of 6 female wild boars per group. Group I animals were administered per os pure zearalenone (ZEN) at 150 μg/kg BW every two months for 7 subsequent days, whereas group II animals received feed naturally contaminated with ZEN at 50 μg/kg BW/day. Female wild boars were exposed to ZEN over a period of 1 year. Control group animals were fed a placebo. Tissue samples (dorsal muscles, left lobe of liver, left kidney, spleen, apical part of the cardiac muscle, cranial lobe of lung, left ovary, central part of the left horn of the uterus) were collected on the last day of the experiment within 3 min after slaughter. In group I, the highest ZEN levels were noted in the spleen (19.813 ng/g), cardiac muscle (18.105 ng/g) and kidneys (14.555 ng/g). In group II, the highest concentrations of ZEN were observed in muscle tissue (12.033 ng/g), uterus (10.821 ng/g) and kidneys (10.463 ng/g). The highest values of the carry-over factor were noted in the same tissues. In the examined female wild boars, per os exposure to natural sources of the parent substance or a combination of ZEN and its metabolites led to different concentrations of ZEN in the analyzed tissues. Zearalenone concentrations were compatible with CF values in both experimental groups. Highlights: Zearalenone and its metabolites can be accumulated in the bodily tissues of female wild boars. The accumulation of zearalenone and its metabolites is probably determined by the degree of oestrogen receptor expression. The highest accumulation levels were observed for α-zearalenol. Zearalenone and its metabolites were accumulated in muscle tissue.